The Relationship Between Learning Outcomes in Social Studies Subjects and Student Learning Motivation - Anggun Tri Mulyana; Adam; La Salim; Wa Ode Selvi Valeria Kinashi (AIQU: Journal Multidiscipliner of Science, 2024)
Teachers need to use learning outcomes as a comprehensive assessment system as part of the teaching and learning process. The purpose of the study is to determine whether a student's motivation to learn and their performance in social studies classes are correlated. Correlational methods are employed in this quantitative study. Twenty-four students participated in this study. In order to gather information for this study, researchers employed documents and questionnaires. The information was then statistically and descriptively analysed. Analytical prerequisite tests, such as regression linearity and data normalcy tests. One type of hypothesis test is the product moment correlation test. The study's findings indicate a meaningful relationship between students' motivation to learn and their performance on learning objectives in social studies classes. Using a correlation value of 0.754 and a learning outcome classification value of 41.67%, and a student learning motivation qualification value of 62.5%, this research shows a relevant correlation between student learning outcomes in social studies lessons and student learning motivation.